Liquidity Ratio Analysis as an Assessment Tool For Measuring Financial Performance at PT.Archi Indonesia. Tbk. - Sinurat, Mangasi; Ilham, Rico Nur (Accounting Progress, 2024)
Companies must observe and analyze company performance in order to survive, one way is by analyze financial performance from the financial side of financial statements. One way to Measuring the level of performance of a company is by measuring the company's liquidity ratio. Financial performance can be seen through financial report data. This research aims to ind out the results of the liquidity ratio analysis of financial performance at PT Archi Indonesia Tbk. The analytical method used in this research is a quantitative method. The results of this research state Analysis of the liquidity ratio at PT.Archi Indonesia seen from the current ratio value, it can be seen that in 2021 the current ratio value of PT. Archi Indonesia Tbk. was found to be 39.30% and increased by 3.96% in 2022, namely 43.26%. This shows that the current ratio of PT. Archi Indonesia in 2022 is considered low/unsafe or has an impact on the company's financial performance, because to spend capital then Archi is obliged to owe another party. The quick ratio shows that in 2021 the quick ratio value of PT. Archi Indonesia Tbk. it was found to be 19.91% and in 2022 it decreased by 1.93% from 2021. In general, this ratio is considered not good and has an impact on the company's financial performance, because it is below 200%, which shows that the company does not have sufficient assets to pay its short-term obligations.